Data envelopment analysis of flood retention area management for a large-scaled catchment: a case study of Huai River basin, China. Issue 1 (31st December 2022) - Zhang, Xiaolei; Ma, Qiang; Xie, Jiabi; Yao, Qiuling; Gourbesville, Philippe; Song, Yuqin
ABSTRACT: According to China's national standard, the design of flood retention areas should cover four hydrological situations associated with 10–100-year return period events, and their capacities should be kept operational for at least 30 years after completion. The Huai River basin is one of the large river basins in China, with an area of 270, 000 km 2 and 31 flood retention areas. To achieve integrated flood management by combining various uses in the flood retention areas, three scenarios were developed for three reference retention areas. The relative efficiency of each flood retention area is assessed using a data envelopment analysis model according to various standards over a period of 35 years after completion. The results show that by considering 10 indexes that refer to flood control capacity and social and economic influences, the partial wetland restoration solution would be the optimal flood management option for the Huai River basin, with highest efficiency. Moreover, by considering the 50-year return period flood standard as the threshold value, maintaining the status quo would be the more efficient approach. This strategy for the sustainable management of flood retention areas in the Huai River basin is promising and can be generalised for other large catchments in China.